The Effects of Mangiferin (Mangifera indica L) in Doxorubicin-induced Cardiotoxicity in Rats - Arozal, W.; Suyatna, F. D.; Juniantito, V.; Rosdiana, D. S.; Amurugam, S.; Aulia, R.; Monayo, E. R.; Siswandi, R. (Drug Research, 2015)
Aim: The cardiotoxicity effect of doxorubicin (DOX), a widely used antitumor agent has restricted its clinical application. The aim of the current study was to explore the potential protective effect of mangiferin, a naturally occurring glucosylxanthone, that have antioxidant activity by its iron-complexing ability in mitochondria, against DOX-induced cardiac toxicity in rats in comparison with other antioxidants namely Sylimarin (SYL) and Vitamin E (VitE).Methods: Mangiferin was given orally to rats at a dose of 50, and 100 mg/kg for 5 weeks, and DOX was injected at a total dose of 15 mg/kg. Cardiac toxicity was evaluated by lactate dehydrogenase and creatine kinase in the serum, malondialdehyde (MDA) level in plasma and cardiac tissue, and antioxidant enzyme superoxide dismutase (SOD) in cardiac tissue.Results: Mangiferin protected against DOX-induced increased mortality and electrocardiogram abnormality and decreased biochemical markers of cardiac toxicity i. e., lactate dehydrogenase and creatine phosphokinase isoenzyme. In addition, elevation of plasma and cardiac tissue levels of MDA in response to DOX treatment were significantly attenuated. The reduction of cardiac activity of SOD was significantly reduced in contrast with the other antioxidant SYL and Vit E. Histopathologically, mangiferin treatment showed significant reduction in inflammatory cell number, fibrotic area, and necrotic foci as compared with DOX only-treated rats.Conclusion: These results suggested that mangiferin had better protective effect against DOX-induced cardiac toxicity in comparison with SYL and VitE, thus besides the antioxidant activity, different mechanism may be involved in the action of mangiferin and need to be clarified in the future studies.
Keywords: mangiferin; doxorubicin; cardiotoxicity; antioxidant